Exchange Rate Regime Transitions - Masson, Paul (IMF Working Papers; Working Paper ;, 2000)
The 'hollowing-out,' or 'two poles' hypothesis is tested in the context of a Markov chain model of exchange rate transitions. In particular, two versions of the hypothesis-that hard pegs are an absorbing state, or that fixes and floats form a closed set, with no transitions to intermediate regimes-are tested using two alternative classifications of regimes. While there is some support for the lack of exits from hard pegs (i.e., that they are an absorbing state), the data generally indicate that the intermediate cases will continue to constitute a sizable proportion of actual exchange rate regimes.